Protektorat Böhmen und Mähren und die Änderungen im Familienrecht - Renata Veselá (Journal on European History of Law, 2024)
The occupation of the Bohemian lands in 1939 led to establishing the Protectorate of Bohemia and Moravia, resulting in the loss of democratic freedoms for Czechs. Different legal statuses were assigned to German Reich citizens, Czechs, and the disenfranchised population targeted by racist legislation. Family law was significantly affected by German regulations and the adoption of the Nuremberg Laws. The discriminatory measures included restrictions on intermarriage and sexual relations. The Catholic Church and international family law provisions also played a role. Further research is needed to fully understand these laws' impact on the Protectorate's societal reality.